First Analysis of Ground-Level Enhancement (GLE) 72 on 10 September 2017: Spectral and Anisotropy Characteristics - A. Mishev; I. Usoskin; O. Raukunen; M. Paassilta; E. Valtonen; L. Kocharov; R. Vainio (SPRINGER, 2022)
Using data obtained with neutron monitors and space-borne instruments, we analyzed the second ground-level enhancement (GLE) of Solar Cycle 24, namely the event of 10 September 2017 (GLE 72), and derived the spectral and angular characteristics of associated GLE particles. We employed a new neutron-monitor yield function and a recently proposed model based on an optimization procedure. The method consists of simulating particle propagation in a model magnetosphere in order to derive the cutoff rigidity and neutron-monitor asymptotic directions. Subsequently, the rigidity spectrum and anisotropy of GLE particles are obtained in their dynamical evolution during the event on the basis of an inverse-problem solution. The derived angular distribution and spectra are discussed briefly.